Effects of blocking ratio and Mach number on aerodynamic characteristics of the evacuated tube train. Issue 1 (2nd January 2020) - Zhou, Peng; Zhang, Jiye; Li, Tian
ABSTRACT: Based on the classical 1-D isentropic theory, the relationship between the critical blocking ratio and the critical incoming flow Mach number in the evacuated tube is deduced in this paper. Next, a simplified 2-D evacuated tube train (ETT) model is used to reveal the distribution characteristics of the flow field in the tube by CFD. The results show that whether the shock waves are fully developed corresponds to whether there is a turning point in the change of ETT drag or wall pressure. The maximum or minimum pressure of the ETT wall has the same trend as that of the tube wall. Linear relationships exist between the ETT drag and the maximum or minimum pressure of the wall and the Mach number after the turning point. Because of the boundary layer around ETT, the maximum and minimum temperatures do not have obvious turning points, but increase with the Mach number.